MILITARY NAMES IN SOUTH AFRICA - QUO VADIS? - Picard, J.H. (Scientia Militaria - South African Journal of Military Studies, 2012)
(ADDRESS DELIVERED AT FIRST MILITARY NAMES CONGRESS HELD AT FORT KLAAPERKOP ON 30 OCTOBER 1993) THE CULTURES OF CLASSES AND MUSTERINGS Traditionally society was divided into four classes: priest, soldier, tradesman and worker, and countries such as India have reflected this division for centuries in their societies, Each of these musterings has over the centuries developed its own culture: the priest by way of ethics, liturgy and religious orders, the soldier with his regimental systems, organisations and traditions, etiquet, terminology and rank hierarchy, the tradesman with his guilds, chambers of commerce, advertising and share markets, the worker with his trade unions and worker associations.